A study on sports and recreational facilities at UiTM Pahang / Zuria Akmal Saad …[et al.] - Saad, Zuria Akmal; Mohamad Nor, Nurul Huda; Said, Abd Razak; Ridzuan, Arifi (2012)
This paper examines the sports and recreational facilities that have been provided at UiTM Pahang. The explored the adequacy, the quality and the overall perception of the sports recreational facilities that has been used by students and staff whether for education or recreational purposes. The findings of this study help the university to be more concerned of the sports recreational facilities' importance at the university. Wrong perception or unseen benefits by the decision maker regarding the cost and benefits in developing the sport facilities making it not a priority to provide even though designing and building these facilities contribute a lot of benefits to the health and performance of the university communities